Designing an E-Guidebook as an Educational and Promotional Media for Kenderan Tourism Village: Integrating Natural and Cultural Tourism Potential - Ni Made Ayuning Pramesti; Putu Herny Susanti; Denok Lestari (PT Inovasi Pratama Internasional, 2026)
This research focuses on designing an E-Guidebook as an educational and promotional digital media to optimize the potential of natural and cultural tourism in Kenderan Tourism Village which has not been maximally exposed due to limited promotional strategies, resources, and information management. This research aims to design an E-Guidebook as an educational and promotional media by listing several natural and cultural tourist attractions in Kenderan Tourism Village. This research uses a qualitative descriptive approach through observation, interviews, and documentation to design an E-Guidebook as an educational and promotional media for the tourism potential of Kenderan Village, with thematic data analysis and presentation of results in the form of descriptive narratives supported by visuals. The results of this study indicate that the design of the E-Guidebook for Kenderan Tourism Village successfully integrates the 4A dimensions as a solution to limited access to information while also functioning as a promotional and educational media based on local wisdom. The results of this study also confirm that the use of digital storytelling and the Multimedia Development Life Cycle approach is able to create interactive media that supports Community Based Tourism (CBT) and strengthens the role of the community in tourism management. The results of this study reveal that the integration of natural and cultural potential through holistic digital representation effectively increases the attractiveness of the destination, the quality of the tourist experience, and the sustainability of tourism in Kenderan Village.